Pengaruh Karakteristik Pengunjung dan Penggunaan Media Komunikasi Pemasaran terhadap Intensitas Kunjungan Agrowisata Taman Bunga Nusantara - Hoesni, Teuku Mufadzal; Saleh, Amiruddin (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2019)
The use of marketing communications media is useful to provide information and promote the uniqueness and superiority of agro-tourism objects and their facilities and activities, thereby increasing the intensity of visits. The objectives of this research is to analyze the characteristics of visitors, to analyze the surgery of marketing communication media, and to analyze the two variables on the intensity of the visit of Taman Bunga Nusantara Agro. The research used quantitative approach with qualitative study method with descriptive explanatory technique. Techniques of data collection using accidental sampling where the researcher determines the respondents spontaneously and based on the population based on predetermined criteria. The results of this study indicate that there is influence of visitor characteristics on the use of marketing communication media and there is influence of visitor characteristics and the use of marketing communication media on the intensity of visits Agrotourism Taman Bunga NusantaraÂ Â Keywords : agro tourism, intensity of visits ,marketing communication, media usage, the charachteristic of visitors Taman Bunga Nusantara